Centering the Right to Health of Childbearing People in the US During the COVID-19 Pandemic - Tomori, Cecília; Penta, Bhavana; Richman, Rebecca (Frontiers in Public Health, 2022)
Childbearing people in the US have experienced the double burden of increased risks from infection and significant disruptions to access and quality of essential health care services during the COVID pandemic. A single person could face multiple impacts across the course of their reproductive trajectory. We highlight how failure to prioritize this population in the COVID-19 policy response have led to profound disruptions from contraception services to vaccination access, which violate foundational principles of public health, human rights and perpetuate inequities. These disruptions continued through the omicron surge, during which many health systems became overwhelmed and re-imposed earlier restrictions. We argue that an integrated pandemic response that prioritizes the healthcare needs and rights of childbearing people must be implemented to avoid deepening inequities in this and future pandemics.